Neenotna praksa prevajanja nazivov pravosodnih organov iz slovenskega v francoski jezik - Kozlevčar, Rastko-Rafael (Podjetje in delo, 2021)
The translation of judiciary titles of the bodies of the Republic of Slovenia from Slovenian to French is confusing, as some translators keep the original Slovene title as if the court were a kind of business entity and we have to deal with a company name, while others apply French titles in order to make the translation more "comprehensive", giving the false impression the organization of courts in Slovenia is utterly similar or even a copy of the judiciary of France. Not to be overlooked are also free-style translations, which can be found on different sites without any reference to the original title. Is it possible to standardize the terminology once for all?
Keywords: francoščina; French; judiciary of Slovenia; nazivi pravosodnih organov Republike Slovenije; pravna terminologija; prevajanje; translation